Management Of Root Canal Treatment In Tooth Pulp Necrosis 25 With Lacerated Roots (Case Report) - Angelita Lewinsky Mahadi; Arny Try Kartinawanty; Cahyani Cahyani; Cecilya Nella Yuppy Anggraeni (CV. AFDIFAL MAJU BERKAH, 2026)
Root canal treatment is an action carried out by removing pulp tissue, both vital and necrotic from the root canal, followed by filling using materials that are suitable for the purpose of cleaning the root canal from necrotic tissue and microorganisms from the root canal. In this case, the final restoration used is a porcelain-fused-to-metal (PFM) crown supported by a fiber core and pegs that can increase resistance to fracture in the tooth after endodontic treatment. A 39-year-old man complained of hollowed left upper back teeth. The patient said that the complaint was felt since 3 years ago in the upper left tooth, there was no pain until the time of examination, food was often tucked and the patient had never done treatment on the tooth. The treatment plan to be carried out is root canal treatment with restoration of the crown of the jacket with fiber pegs in the root canal in the case of tooth pulp necrosis 25 with lacerated roots. The three main stages in root canal treatment are known as the endodontic triad, namely biomechanical preparation, sterilization, and hermetic root canal obturation. The purpose of root canal treatment is to eliminate pathogenic microorganisms and infected pulp tissue from within the root canal, prevent the formation of toxic products, as well as protect periapical tissue.